2011
DOI: 10.1002/gcc.20915
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic polyclonality of breast carcinomas: Association with Clinico‐Pathological Characteristics and Outcome

Abstract: Routinely used prognostic factors fail to predict clinical outcome in a significant proportion of breast cancer patients, implying that they can not detect some important biological characteristics. Chromosomal changes have been described in breast carcinomas for many years but their significance is not clear. We compared chromosomal changes with clinico-pathological characteristics and clinical outcome in 203 breast cancer patients with a follow-up of 9-18 years. Combining data from classical cytogenetics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Due to the chosen technique, only duplications and deletions are described in this study, while balanced structural changes remain undetected. Each patient displayed an almost unique pattern of aberrations which is consistent with the idea of the multi-causation of cancer and findings of spontaneous abnormalities in normal human fibroblasts from patients with Li-Fraumeni cancer syndrome [39] and chromosomal changes in non-cancerous breast tissue for breast carcinoma patients [40]. Interestingly, an abnormal gene expression in fibroblasts was detected in patients with Gorlin syndrome (GS), which is a hereditary disorder with tumorigenicity, caused by constitutive hyperactivity of hedgehog signaling.…”
Section: Copy Number Variation In Cancer Patientssupporting
confidence: 81%
“…Due to the chosen technique, only duplications and deletions are described in this study, while balanced structural changes remain undetected. Each patient displayed an almost unique pattern of aberrations which is consistent with the idea of the multi-causation of cancer and findings of spontaneous abnormalities in normal human fibroblasts from patients with Li-Fraumeni cancer syndrome [39] and chromosomal changes in non-cancerous breast tissue for breast carcinoma patients [40]. Interestingly, an abnormal gene expression in fibroblasts was detected in patients with Gorlin syndrome (GS), which is a hereditary disorder with tumorigenicity, caused by constitutive hyperactivity of hedgehog signaling.…”
Section: Copy Number Variation In Cancer Patientssupporting
confidence: 81%
“…Studies of breast cancer karyotypes have demonstrated that this type of cancer frequently has the structural genomic aberrations as seen in other forms of human cancer, including aneuploidy. [4][5][6][7] Furthermore, several previous studies have shown variability of chromosome numbers from cell to cell within a given breast cancer, [8][9][10][11] suggesting that breast cancers also have chromosomal instability.…”
Section: Introductionmentioning
confidence: 99%